The metabolic network of the last bacterial common ancestor - Joana C. Xavier (Nature Portfolio, 2021)
Joana C. Xavier, Rebecca E. Gerhards and colleagues reconstruct the habitat and lifestyle of the last bacterial common ancestor (LBCA) through the construction of the metabolic network and gene tree analysis of 146 LCBA protein families. Their analyses indicate that the LBCA was rod-shaped, and that the first lineage to diverge from the ancestral bacterial stem was most similar to modern Clostridia, followed by other autotrophs that harbor the acetyl-CoA pathway.